2018
DOI: 10.2166/wst.2018.431
|View full text |Cite
|
Sign up to set email alerts
|

Anammox start-up strategies: the use of local mixed activated sludge seed versus Anammox seed

Abstract: The start-up period of Anammox systems is still a big challenge due to the unavailability of large volumes of slowly growing Anammox seed locally in most countries. This study aims to evaluate the effects of seeding strategy on the start-up and enrichment period of Anammox systems by monitoring both process performance and microbial population dynamics. Two different seeding strategies, the use of mixed activated sludge culture from a local STP and the use of enriched Anammox culture transported from abroad, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 17 publications
2
1
0
3
Order By: Relevance
“…In P3, there was evidence of simultaneous NH 4 + -N and NO 2 − -N consumption with noticeable anammox activity in the later stage of the phase. The sudden onset of greater anammox activity was consistent with the results of previous studies in which anammox reactors were variously inoculated with anaerobic granular sludge [46], denitrification sludge [47], activated sludge [48], and their mixture [33,34]. We infer that this increased activity was due to quorum sensing by AnAOB, in which anammox activity occurs only when the cell density is higher than a threshold value (10 10 -10 11 /mL) [49].…”
Section: Nitrogen Removal Performance In Enrichment Periodsupporting
confidence: 90%
See 1 more Smart Citation
“…In P3, there was evidence of simultaneous NH 4 + -N and NO 2 − -N consumption with noticeable anammox activity in the later stage of the phase. The sudden onset of greater anammox activity was consistent with the results of previous studies in which anammox reactors were variously inoculated with anaerobic granular sludge [46], denitrification sludge [47], activated sludge [48], and their mixture [33,34]. We infer that this increased activity was due to quorum sensing by AnAOB, in which anammox activity occurs only when the cell density is higher than a threshold value (10 10 -10 11 /mL) [49].…”
Section: Nitrogen Removal Performance In Enrichment Periodsupporting
confidence: 90%
“…In our previous, we found that AnAOB showed resistance to lanthanum (La)(III)-a major REE found in stream and groundwater nearby REE mining areas, which indicated that anammox may make difference in the in situ bioremediation [22]. However, anammox wastewater treatment reactors are usually started up by inoculating with enough anammox sludge, partial nitrification sludge, ordinary nitrification sludge or their mixture, which were harvested from some other stably operated reactor or plants [26,[32][33][34][35][36]. Thus, low-temperature preservation during long-distance is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Для виявлення анаммокс бактерій (анаеробне хемолітотрофне окиснення амонію) використовували мінеральне поживне середовище [112] наступного складу (г/л): (NH4)2SO4 -0,0514; NaNO2 -0,024; NaNO3 -0,010; KHCO3 -1,248; NaH2PO4 -0,05; CaCl2 -0,3; MgSO4 -0,2; FeSO4 -0,006; EDTA -0,006 [119]. Посіви інкубували 4 доби (на четверту добу кількість газу, що виділився, складала 70 мл).…”
Section: виявлення анаммокс бактерійunclassified
“…Для визначення наявності АНАМОКС процесу в отриманій пробі використовували живильне мінеральне середовище, де концентрація солі амонію і нітриту була на рівні отриманих даних хімічного аналізу дослідної проби. Склад живильного середовища (г/л): (NH 4 )2SO 4 -0,0514; NaNO 2 -0,024; NaNO 3 -0,010; KHCO 3 -1,248; NaH 2 PO 4 -0,05; CaCl 2 -0,3; MgSO 4 -0,2; FeSO 4 -0,006; EDTA -0,006 [9]. Хімічну колбу 500 мл заповнювали 350 мл живильного мінерального середовища, і потім у неї завантажували 70 мл рідкого осаду мулу з проби та закривали пробкою з отвором для виведення газу.…”
Section: матеріали та методиunclassified
“…Далі отриману суспензію продували протягом 20 хвилин газом Ar / CO 2 (95% / 4,5%) для видалення розчиненого кисню та отримання анаеробних умов. Колбу поміщали в термостат при температурі 32 °С до появи в ній бульбашок газу [9,1]. рН утримували на рівні 7,6, використовуючи 1M NaOH і 1% H 2 SO 4 з підтриманням та відновленням анаеробних умов.…”
Section: матеріали та методиunclassified